Stochastische Simulation von Energieflüssen im NutzfahrzeugEin einsatzorientiertes Bewertungs- und Optimierungsverfahren - Oberfell, Ralf (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
This book proposes a stochastic simulation process as an efficient approach to consumption simulation. The process complements the explicit transient analysis. Thereby, it takes into account statistically evaluated vehicle and route data and calculates a probability distribution of the energy savings which can be achieved by specific measures.